Gas hydrate formation phase boundary behaviour of synthetic natural gas system of the Keta basin of Ghana - Broni-Bediako, E. (Bentham Science Publishers B.V., 2017)
Background: Gas hydrates are considered as a major threat to the oil and gas flow assurance industry. At high pressure and low temperature conditions, gas hydrates form in pipelines and production facilities leading to pipeline blockages, high removal cost, environmental hazards and loss of lives. For a successful prevention of gas hydrate formation, predicting the hydrate formation phase boundary of hydrocarbon fluid composition becomes very necessary. Objective and Method: In this study, computer simulation software called PVTSim was used to predict hydrate formation phase boundary of synthetic natural gas composition in the Keta basin of Ghana at pressures and temperatures range of 43.09 bar - 350 bar and 12.87 °C - 27.29 °C respectively. The effect of changes in natural gas composition (N2 and H2S) and the presence four commonly used thermodynamic gas hydrate inhibitors (methanol, ethanol, diethylene glycol and monoethylene glycol) on the hydrate formation phase boundary is also discussed. Prior to the study, the accuracy of PVTSim was validated with the hydrate formation phase data in literature. Results and Conclusion: Results suggested that the hydrate formation phase boundary decreased with increasing N2 composition and increased with increasing H2S composition, suggesting that, the presence of H2S increases the threat of hydrate formation. However, a reduction in hydrate formation threat was observed in the presence of all four commonly used gas hydrate thermodynamic inhibitors with methanol demonstrating the highest inhibition effect. © 2017 Broni-Bediako et al.